2010
DOI: 10.1002/cne.22302
|View full text |Cite
|
Sign up to set email alerts
|

Telencephalic binding sites for oxytocin and social organization: A comparative study of eusocial naked mole‐rats and solitary cape mole‐rats

Abstract: African mole-rats provide a unique taxonomic group for investigating the evolution and neurobiology of sociality. The two species investigated here display extreme differences in social organization and reproductive strategy. Naked mole-rats (NMRs) live in colonies, dominated by a queen and her consorts; most members remain nonreproductive throughout life but cooperate in burrowing, foraging, and caring for pups, for which they are not biological parents (alloparenting). In contrast, Cape mole-rats (CMRs) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 112 publications
(176 reference statements)
4
65
0
Order By: Relevance
“…A blockade of Oxt receptors in the nucleus accumbens of female prairie voles inhibits spontaneous maternal behavior, and Oxt receptor densities in this nucleus also are positively correlated with individual differences in the expression of parental behaviors (Olazabal and Young, 2006a;2006b). Although it is not known whether Oxt plays a similar role in the nucleus accumbens of naked mole-rats, a preliminary report suggests that Oxt receptors are found in the nucleus accumbens of naked mole-rats but not of a solitary mole-rat species with no communal care of the young (Kalamatianos et al, 2007). Given the individual differences in Oxt receptor distribution and maternal responsiveness in voles, it would be interesting in future studies to compare Oxt and Oxt receptors in young, small naked mole-rate subordinates, which tend to be more active participants in pup care, with that in older, larger subordinates, which often specialize in colony defense .…”
Section: Discussionmentioning
confidence: 99%
“…A blockade of Oxt receptors in the nucleus accumbens of female prairie voles inhibits spontaneous maternal behavior, and Oxt receptor densities in this nucleus also are positively correlated with individual differences in the expression of parental behaviors (Olazabal and Young, 2006a;2006b). Although it is not known whether Oxt plays a similar role in the nucleus accumbens of naked mole-rats, a preliminary report suggests that Oxt receptors are found in the nucleus accumbens of naked mole-rats but not of a solitary mole-rat species with no communal care of the young (Kalamatianos et al, 2007). Given the individual differences in Oxt receptor distribution and maternal responsiveness in voles, it would be interesting in future studies to compare Oxt and Oxt receptors in young, small naked mole-rate subordinates, which tend to be more active participants in pup care, with that in older, larger subordinates, which often specialize in colony defense .…”
Section: Discussionmentioning
confidence: 99%
“…As with social voles, OXT receptor levels in naked molerats are intense and extensive in the nucleus accumbens, whereas OXT receptors are not detectable in the Cape mole-rat in this area [32]. This abundance of OXT receptor levels in the nucleus accumbens of naked mole-rats reflects their high levels of sociality, alloparenting behaviour and potential for reproductive attachments, whereas the reduced oxytocinergic signalling at this site in Cape mole-rats reflects a paucity of prosocial behaviours.…”
Section: Proximate Factors (A) Neurobiology Of Social Behaviourmentioning
confidence: 96%
“…This abundance of OXT receptor levels in the nucleus accumbens of naked mole-rats reflects their high levels of sociality, alloparenting behaviour and potential for reproductive attachments, whereas the reduced oxytocinergic signalling at this site in Cape mole-rats reflects a paucity of prosocial behaviours. Furthermore, there is a remarkable correspondence between the OXT receptor levels in some areas of the brain in the eusocial naked mole-rat and the monogamous and pair-bonding prairie vole at one end of the spectrum, and the asocial Cape mole-rat and the solitary, non-pair-bonding and promiscuous voles at the other [28,32]. Recent studies have confirmed that the Damaraland mole-rat also resembles the naked mole-rat (and social voles) with respect to OXT receptor binding being present in the nucleus accumbens.…”
Section: Proximate Factors (A) Neurobiology Of Social Behaviourmentioning
confidence: 99%
“…In the case of prairie voles, oxytocin binding in certain regions, particularly the nucleus accumbens, is crucial to the maintenance of monogamous attachments Liu and Wang, 2003), suggesting a potentially broad functional significance to species differences in the anatomical distribution of this receptor. More recently, it has become apparent that other animals such as tuco-tucos, mole-rats, singing mice and even estrildid finches demonstrate interspecific differences in OTR distribution together with differences in social and/or reproductive organization (Beery et al, 2008;Campbell et al, 2009;Goodson et al, 2009;Kalamatianos et al, 2010;Anacker and Beery, 2013).…”
Section: Introductionmentioning
confidence: 99%